Performance comparison of the wavenumber and spatial domain techniques for mapping basement reliefs from gravity data - Pham Luan Thanh; Eldosouky Ahmed M.; Gómez-Ortiz David; Duong Van-Hao; Abdelrahman Kamal; Alzahrani Hassan (Open Geosciences, 2021)
Estimating the density interface depth is an important task when interpreting gravity data. A range of techniques can be applied for this. Here we compare the effectiveness of the wavenumber and spatial domain techniques for inverting gravity data with respect to basement reliefs. These techniques were tested with two synthetic gravity models, and then applied to a real case: the gravity data of the Magura basin (East Slovakian Outer Carpathian). The findings show that the spatial domain technique can precisely estimate the structures, but the computation speed is slow, while the wavenumber domain technique can perform faster computations with less precision.